Usability And Educational Impact Of A Gamified Board Game In Secondary Education - Shalinawati Ramli; Nurul Azmawati Mohamed; Mohd Dzulkhairi Mohd Rani; Shahlan Surat; Azman Ab. Rahman (EL-MED-Pub Publishers, 2025)
Gamification has emerged as an effective strategy for enhancing student engageDemo-4976-Article textDemo-4976-Article textment and learning experiences. Board games, as a gamified approach, provide interactive learning opportunities by integrating subject content with structured gameplay. The Global Kesihatan Game (GKG) was developed to improve students' understanding of science, physical education, and health while promoting active participation. This study evaluates the usability and educational value of GKG as a teaching aid. A descriptive cross-sectional study was conducted over two months at a Malaysian secondary educational institution affiliated with a government university. A total of 42 students aged 13 to 16 years participated in the study. Students engaged in the GKG board game in groups, following predefined rules that encouraged collaboration and strategic thinking. Data were collected via an online survey, assessing the game’s design, usability, engagement, and impact on learning. The findings indicate that GKG effectively enhances student engagement, with participants reporting increased interest and enjoyment in learning. The game was perceived as visually appealing, easy to understand, and well-integrated with curriculum content. While GKG facilitated knowledge acquisition in science and health, some students suggested further refinement to improve conceptual depth and clarity. The game also encouraged social interaction and collaborative learning. The GKG board game is a valuable educational tool that promotes engagement and enhances learning in science and health subjects. While the game demonstrates strong usability, minor refinements in content complexity and instructional depth could further optimize learning outcomes. Future research should explore long-term impacts of gamification on academic performance and cognitive skills.